2011
DOI: 10.1051/0004-6361/201015886
|View full text |Cite
|
Sign up to set email alerts
|

Sub-arcsecond [Fe ii] spectro-imaging of the DG Tauri jet

Abstract: Context. The origin of protostellar jets as well as their impact on the regulation of angular momentum and the inner disk physics are still crucial open questions in star formation. Aims. We aim to test the different proposed ejection processes in T Tauri stars through high-angular resolution observations of forbidden-line emission from the inner DG Tauri microjet. Methods. We present spectro-imaging observations of the DG Tauri jet obtained with SINFONI/VLT in the lines of [Fe ii]λ1.64 μm, 1.53 μm with 0. 15 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
111
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(122 citation statements)
references
References 57 publications
10
111
0
1
Order By: Relevance
“…However, this only extends out a few AU from the rotation axis, then the Kep- Red is OP, green is µ = −0.12, blue is BP, and purple is PP. In the mass flux figure, we also overplot the observed mass flux in DG tau from Agra-Amboage et al (2011) for the high (HVB) and medium velocity (MVB) blueshifted intervals. The µ = −0.12 jet has the highest mass flux, but because the OP jet is faster, the two have similar momentum and the OP jet has the higher jet power.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this only extends out a few AU from the rotation axis, then the Kep- Red is OP, green is µ = −0.12, blue is BP, and purple is PP. In the mass flux figure, we also overplot the observed mass flux in DG tau from Agra-Amboage et al (2011) for the high (HVB) and medium velocity (MVB) blueshifted intervals. The µ = −0.12 jet has the highest mass flux, but because the OP jet is faster, the two have similar momentum and the OP jet has the higher jet power.…”
Section: Discussionmentioning
confidence: 99%
“…The mass flux in the PP jet is lower than the mass flux in the BP jet throughout. The observed mass flux in the DG tau jet (taken from Agra-Amboage et al 2011) is also shown in Fig. 15.…”
Section: Jet Rotation Far From the Sourcementioning
confidence: 93%
“…Our toy models favor a slightly larger spatial scale along the jet axis R max 60 AU, givingṀ w ∼ 10 −9 M yr −1 . With an estimated accretion rate ofṀ acc = (3 ± 2) × 10 −7 M yr −1 over the period (Agra-Amboage et al 2011, the ejectionaccretion ratio in the blue lobe of the molecular wind would thus be 0.003-0.014. This would be consistent with the lever arm parameter λ = 13 of the MHD disc wind solution if the external launch radius, r e , and internal launch radius, r i , for the molecular streamlines are in a ratio r e /r i 1.15-2 (see, e.g., Eq.…”
Section: Molecular Mhd Disc Wind Heated By Ambipolar Diffusionmentioning
confidence: 99%
“…Tails are meant to represent the wind lifted from the disk. Coaxial low velocity, wider winds seen in [H 2] lines are observed in many stellar outflows in the IR spectral range (see, e.g., Takami et al 2004;Agra-Amboage et al 2011). As an example, Takami et al (2004) reports a molecular outflow from DG-Tau thermalized at 2000 K that extends up to ∼50 AU from the jet axis in the transverse direction.…”
Section: The "Tails"mentioning
confidence: 99%
“…Finally, in both cases the interpretation of the jet spectra is made difficult by projection effects along the line of A&A 567, A13 (2014) sight. Nevertheless, valuable observational studies at high resolution and in different wavelengths have successfully investigated the properties of the jets in the acceleration region immediately downstream from the collimation zone, between ∼10 and 100 AU from the star, and have provided important constraints to the launch process (e.g., Bacciotti et al 2000;Woitas et al 2002;Melnikov et al 2009;Coffey et al 2008;Takami et al 2004;Pyo et al 2003Pyo et al , 2006Hartigan & Morse 2007;Agra-Amboage et al 2011). The only way to connect the observed region to the launch zone, however, is to create a logical link via numerical studies.…”
Section: Introductionmentioning
confidence: 99%